A correlative study of the allantois in pig and rabbit highlighting the diversity of extraembryonic tissues in four mammalian species, including mouse and man. (6th February 2017) - Hassan, Waad; Viebahn, Christoph
Abstract: Despite its conserved role in placenta and umbilical cord formation, the mammalian allantois shows remarkable diversity in size and form as well as in the timing of its appearance and attachment to the chorion. In the mouse, the common allantoic diverticulum is lacking; instead, the allantoic core domain is defined as a progenitor center for allantoic development. In this study, the allantoises of the pig and the rabbit as two nonrodent mammals of increasing significance in biomedical research are compared (1) morphologically using high resolution light and electron microscopy and (2) molecularly using brachyury mRNA expression as a mesodermal marker. Multiple small allantoic diverticula in the rabbit contrast with a single large cavity filling the entire allantois of the pig, but neither pig nor rabbit allantois expresses brachyury . The mesothelium on the allantois surface shows regional variability of cell contacts and microvilli, while blood vessels appear randomly around the allantoic diverticula in a mesodermal layer of variable thickness. Primordial germ cell‐like cells are found in the allantois of the pig but not of the rabbit. To understand further the relevance of this developmental and morphological diversity, we compare the allantois development of pig and rabbit with early developmental landmarks of mouse and man. Our findings suggest that (1) tissue interaction between endoderm and mesoderm is important for allantoic development and vascular differentiation in species with a rudimentary allantoic diverticulum, (2) allantoic mesothelium plays a specific role in chorioallantoic attachment, allantoic differentiation and vascularization, and (3) there is a pronounced diversity in the extraembryonic migratory pathways of primordial germ cells among mammals. Finally, the phylogenetically basal characteristics of the pig allantois are suggestive of a functional similarity in mammals with a large allantois before placentation and in (aplacental) sauropsids with a chorioallantoic membrane well‐adjusted to material exchange function. Abstract : The diversity of the mammalian allantois is known to be different in size and form. Here, we show, in addition, (1) specific characteristics of the endodermal component accompanied by mesoderm and early blood vessels (bv) and surrounded by mesothelium with diversified cell contacts and microvilli, (2) interspecific differences in Brachyury expression, and (3) specific presence and absence of cells resembling primordial germ cells (pgc). We propose a hitherto unsuspected variation (a) in allantoic function prior to placenta formation, and (b) in mechanisms of the allantoic development through tissue interactions.